Pola Komunikasi Terapeutik Pembimbing dalam Menumbuhkan Kemandirian Anak Tunagrahita di Panti PSDI Raharjo Sragen - Wijayanti, Christina Nur; Mawardiningsih, Wahjoe; Damar Pratiwi, Hastian (JURNAL KOMUNITAS, 2024)
Therapeutic communication is a communication effort aimed at healing the patient. However, for mentally retarded children, therapeutic communication functions to foster independence. Mentally retarded children are children with special needs who have limitations in their intelligence and social functions. This research aims to find out how interpersonal and therapeutic communication patterns occur in the process of forming the independence of mentally retarded children. The research method used is descriptive research. Where data collection techniques use observation, interviews and documentation. Meanwhile, the data analysis technique uses triangulation analysis method. From the research that has been conducted, it is known that Panti PSDI Raharjo has implemented therapeutic communication through interpersonal communication to foster the independence of mentally retarded children. Regarding interpersonal communication patterns, supervisors use a constructivist approach. This approach helps children to support the exploration of children's abilities and development. Meanwhile, in therapeutic communication, supervisors use two types of communication, namely verbal and non-verbal. This makes communication more effective and maximal in fostering independence. From the explanation of the research results above, it can be concluded that the pattern of interpersonal communication that occurs at the PSDI Raharjo Home goes well, thus encouraging the success of therapeutic communication carried out by the supervisors, although in its implementation there are still several obstacles, but the supervisors are able to overcome these obstacles well, so that the process develop children's independence smoothly.